The Effect of Labor and Capital on the Development of MSME Income in Medan City - Ariesa, Y.; Tantono, N.; Yenni, Yenni; Gracia, Gracia (Budapest International Research and Critics University, 2021)
MSMEs are the main driving force for the economy because MSMEs are a benchmark for improving the quality of the economy both in terms of income and labor. So that economic development is needed in advancing the MSME sector, especially as a provider of consumer needs during the pandemic, because at this time people need a variety of daily household needs that are easily accessible in the surrounding environment. One of the most basic big problems in increasing the development of MSME income is capital. Capital is the first point in the development of an MSME business process. The main problem faced is the lack of a workforce with adequate qualifications, especially in the annual report monitored by the Medan City Government. Using quantitative research based on the effect of labor and capital on income. Sampling with the purposive sampling method. The results showed that there was a positive and significant effect of labor and capital on income.